The Analysis of Hygiene, Hazard Analysis, and Critical Control Point Purchasing Department at Four Seasons Hotel Jakarta in Ensuring Food Safety for Guests - Demolingo, Ramang; Fitri Afianti, Azzachra (Akademi Komunitas MAPINDO, 2022)
This study aimed to understand (1) The application of Hygiene using hazard analysis and critical point (HACCP) systems in Purchasing Department. (2) Ensuring the safety of hotel food by implementing HACCP system onto their hygiene procedure. This study used descriptive qualitative design that describes the data that have been collected through observation, interviews, documentation matrix analysis IFE and EFE during the research. The results of this study indicate that Four Seasons Hotel Jakarta has implemented the hygiene standart accordance with the Hazard Analysis and Critical Control Point (HACCP) system. In carrying the activities at Purchasing Department, Four Seasons Hotel Jakarta still faces many problems. To overcome the problems Purchasing Department Manager have several strategies efforts to overcome them. Keywords: Hygiene, Purchasing, HACCP, Hotel